Randomized Control Trial Study of K-3 Students Demonstrates Greater Scantron Reading Assessment Performance for Imagine Language & Literacy Users - Berrett, Andrew; Fontanet, Nathan; Carter, Nari (JOURNAL OF ADVANCES IN LINGUISTICS, 2022)
Supplemental education technology tools such as those that provide computer-assisted instruction may provide important academic value to elementary age students in developing literacy and language skills. A randomized control trial of students within five schools was conducted in a northwestern school district in the United States of America to evaluate the academic impact of the Imagine Language & Literacy program on student literacy outcomes. In one school, K–3 students who used the program were found to have achieved test scores that were significantly greater than students who did not use the program during the 2013–2014 school year. The results of this study provide evidence of the effectiveness of supplemental literacy tools such as Imagine Language & Literacy in improving student outcomes in literacy development.